2018
DOI: 10.1088/1361-6420/aaf129
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of structural similarity and regularization for joint inverse problems governed by PDEs

Abstract: Joint inversion refers to the simultaneous inference of multiple parameter fields from observations of systems governed by single or multiple forward models. In many cases these parameter fields reflect different attributes of a single medium and are thus spatially correlated or structurally similar. By imposing prior information on their spatial correlations via a joint regularization term, we seek to improve the reconstruction of the parameter fields relative to inversion for each field independently. One of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 36 publications
1
14
0
Order By: Relevance
“…Resulting capabilities have enabled the use of UQ methods in complex problems of physical relevance, including e.g. transport in porous media [110,111], seismic sensing [112], fluid dynamics [62,113,114], chemistry [115,116], reacting flow [117], and materials [118,119], spanning applications in geophysics, combustion, and climate.…”
Section: G Uncertainty Quantificationmentioning
confidence: 99%
“…Resulting capabilities have enabled the use of UQ methods in complex problems of physical relevance, including e.g. transport in porous media [110,111], seismic sensing [112], fluid dynamics [62,113,114], chemistry [115,116], reacting flow [117], and materials [118,119], spanning applications in geophysics, combustion, and climate.…”
Section: G Uncertainty Quantificationmentioning
confidence: 99%
“…Notable examples are PET and MRI (PET/MRI) [5052], PAT and US [53], geophysics applications with multiple data (e.g. electromagnetic waves, seismic waves, radar, DC resistivity, groundwater flow) [5461]. MMMI: Coupled Physics Imaging (CPI).…”
Section: A Taxonomy Of Problemsmentioning
confidence: 99%
“…We note that this function and its gradients are additive, leading to an optimization procedure that is uncoupled in theory, and the different parameter updates and the forward problem solutions do not mutually influence each other. Recent studies (Crestel et al 2018) have suggested introducing an explicit coupling via, e.g. cross-gradient or density-norm regularization.…”
Section: Combining Cost Functionsmentioning
confidence: 99%
“…By design we consider that an increase in the viscosity has to mimic an increase in the density and the wave speed, and vice versa. The same behavior can also be achieved by adding a regularization that opts to optimize the cross product of the gradients, by imposing a penalty on points where the gradients point in different directions-an approach that is described in more detail elsewhere (e.g., Crestel et al 2018).…”
Section: Collinear Gradient Updatesmentioning
confidence: 99%